Hanbelî mezhebinin teşekkül süreci - Efe, Halil (My University, 2022)
Hanbelî mezhebi, günümüzde hayatiyetini sürdüren dört Sünnî fıkıh mezhebinden biridir. Seçkin hadis âlimi Ahmed b. Hanbel'in (v. 241/ 855) fıkıh anlayışı ve fıkhî görüşleri, Hanbelî mezhebinin esasını teşkil etmiştir. Bununla birlikte mezhep, İbn Hanbel'in öğrencileri ve onları takip eden fakihlerin mesaileriyle teşekkül etmiştir. Onlar, İbn Hanbel'in fıkhî görüşlerini rivayet, tedvin ve tasnif ettiler. Bu görüşleri, bir fıkıh doktrini teşkil etmek üzere sıhhat, geçerlilik ve tutarlılık cihetlerinden incelediler. Nihayet İbn Hanbel'in ictihad metodolojisini tespit ettiler. Müteakip üç neslin tedvin, tasnif ve inşâ olarak niteleyebileceğimiz fıkhî mesaileri, hicrî IV. asrın son çeyreğinde, fıkıh doktrini ve ictihad metodolojisi tespit edilmiş bir Hanbelî mezhebinden söz etmeyi mümkün kılmıştır.

The Ḥanbalī madhhab is one of the four Sunnī schools of law that are still alive today. The outstanding ḥadīt̲h̲ scholar Ahmad b. Ḥanbal's (d. 241/ 855) thought of fiqh and his legal opinions constituted the basis of the Ḥanbalī school. However, the Ḥanbalī school was formed by the efforts of Ibn Ḥanbal's students and the jurists who followed them. They narrated, compiled and classified Ibn Ḥanbal's legal opinions. They examined these opinions in terms of their soundness, validity and consistency to constitute a legal doctrine. Finally, they identified Ibn Ḥanbal's ijtihād methodology. The efforts of the successive three generations, which we can describe as tadvīn (compilation), tasnīf (classification) and inshā (construction), made it possible to talk about a Ḥanbalī school whose legal doctrine and ijtihād methodology were identified in the last quarter of the fourth / tenth century.
Keywords: Ahmed b. Hanbel; Formation; Hanbelî Mezhebi; Islam; Islamic law; İslam; İslam hukuku; Legal Responsa; Mesail Aḥmad Ibn Ḥanbal; Teşekkül; The Ḥanbalī School of Law